Early Christian-Muslim debate on the unity of God: three Christian scholars and their engagement with Islamic thought (9th century c.e.) - Husseini, Sara Leila (History of Christian-Muslim relations, 2014)
In Early Christian-Muslim Debate on the Unity of God, Sara Husseini examines the writings of three ninth century Christian theologians, analysing their engagement with Islamic theology in order to articulate the doctrine of the Trinity in an Arabic Islamic context